(3GdaJGhi GdRjfjI aj abg GdMfajIs - (3Rjf GdOjf Hf EHQGgje Hf eMeO Hf fLje GdeUQj GdMfaj , GHf fLje,J (B970 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOkG def CHQR GdYGde Ydi CMSf JQJjH hfXGe , hCfTC OYGFe Cgd GdeYGQa adg GdaVd GdYGe s
(3BNQgG (B:s
(3ddRhL GdQHY hdcd hGMO ef GdCHhjf GdSOS hGdHGbi ddhdO dGZjQ hGddg JYGdi CYde , Sdc Gddg HfG hHce GdWQjb GdCSde hCLGQfG hEjGce ef MQ fGQLgfe hYdefG Yde eGde fYde eMeO Udi Gddg Ydjg hSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQSJ HGdCHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B192 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B378s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1223s
Keywords: (3Gdabg GdMfajs